2015
DOI: 10.1016/j.jmoldx.2015.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Center for Personalized Cancer Care at a Regional Cancer Center

Abstract: Next-generation sequencing (NGS) capabilities can affect therapeutic decisions in patients with complex, advanced, or refractory cancer. We report the feasibility of a tumor sequencing advisory board at a regional cancer center. Specimens were analyzed for approximately 2800 mutations in 50 genes. Outcomes of interest included tumor sequencing advisory board function and processes, timely discussion of results, and proportion of reports having potentially actionable mutations. NGS results were successfully gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…However, the integration of such technology in a practical, efficient, and value-added manner is not straightforward. Some reports are upcoming for American hospitals involving small and heterogenous population of patients with different cancer location [27][28][29][30][31]. While many clinical trials on this subject are in progress in European countries, no European hospital has reported their experience with such strategy in a daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, the integration of such technology in a practical, efficient, and value-added manner is not straightforward. Some reports are upcoming for American hospitals involving small and heterogenous population of patients with different cancer location [27][28][29][30][31]. While many clinical trials on this subject are in progress in European countries, no European hospital has reported their experience with such strategy in a daily clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…The authors demonstrated that 63% of the patients carried clinically relevant mutations, with 26% displaying a mutation with therapeutic implications [242]. A second survey on 2221 cases from the Foundation of Medicine (Foundation Medicine ® , Cambridge, MA, USA) also concluded that actionable mutations were identified in 76% of the subjects and results were further confirmed in independent investigations [157,184,236,251,252,253,254]. …”
Section: Cancer Somatic Mutation Analysismentioning
confidence: 99%
“…A pragmatic approach can be not to focus on each disease/each mutation subset but to use rather the so called basket trial, where different tumour types having the same genetic alteration are included and through a specific study design “baskets” are enriched for patients with a specific tumour type or histology [260]. In addition to these strategies and innovative study designs, committees are established to make treatment recommendations like the “Molecular Tumor Board” [253] and the US Personalized Health Care Committee [194]. …”
Section: Limitations and Complications Of Ngs In Genetic Diagnostimentioning
confidence: 99%
“…ese tumor cells grow on their own through ingestion of nutrients from the outside of the body (naturally without any specific major cause) or by other factors (drinking alcohol, smoking, etc.). Cancerous cells can go anywhere through the blood, and when the moved cancer cells are malignant, they can cause damage to other tissues around them [1,2].…”
Section: Introductionmentioning
confidence: 99%